2022
DOI: 10.3390/ijerph191610097
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress among Hospitalized COVID-19 Patients in Denmark during the First 12 Months of the Pandemic

Abstract: This study aimed to investigate psychological distress among patients hospitalized with a COVID-19 diagnosis in Denmark during the first 12 months of the pandemic and to assess changes in psychological distress in the three months following discharge. A single-center prospective observational survey study among patients hospitalized with a COVID-19 diagnosis between May 2020 and May 2021 was conducted. Participants completed a survey at three time points: at admission, and 1 and 3 months after discharge. Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
1
8
1
2
Order By: Relevance
“…The gradual adaptation process was reflected in COVID-19 patients' attitudes upon admission, from uncertainty about the disease to anticipation and suspicion of the examinations, to confrontation and acceptance following the diagnosis, which ultimately culminated in gratitude for the experience ( 14 ). This study also identified a significant reduction in symptom burden associated with depression and anxiety over time with hospitalization ( 15 ). However, cases who had been gradually improving physically and psychologically with the treatment appeared to experience changes in their psychological state after experiencing a re-positive result.…”
Section: Discussionmentioning
confidence: 77%
“…The gradual adaptation process was reflected in COVID-19 patients' attitudes upon admission, from uncertainty about the disease to anticipation and suspicion of the examinations, to confrontation and acceptance following the diagnosis, which ultimately culminated in gratitude for the experience ( 14 ). This study also identified a significant reduction in symptom burden associated with depression and anxiety over time with hospitalization ( 15 ). However, cases who had been gradually improving physically and psychologically with the treatment appeared to experience changes in their psychological state after experiencing a re-positive result.…”
Section: Discussionmentioning
confidence: 77%
“…Twelve studies 17,22,24,26,29,33,34,36,42,44,45,47 used 12 different mental health-related measures: the Patient Health Questionnaire-9 (PHQ-9; N = 3), the Hospital and Anxiety Depression Scale (HADS; N = 2), Generalised Anxiety Disorder-7 (GAD-7; N = 2), the Beck Anxiety Inventory (BAI; N = 1), the Beck Depression Inventory (BDI; N = 1), the Child Depression Inventory (CDI, N = 1), the Child Post-Traumatic Stress Reaction Index (CPTS-RI; N = 1), the Harvard Trauma Questionnaire (HTQ; N = 1), the Perceived Stress Scale (PSS-10; N = 1), the Screen for Child Anxiety Related Disorders (SCARED; N = 1), the Self-Rating Anxiety Scale (SAS; N = 1) and the Self-Rating Depression Scale (SDS; N = 1). Twelve studies used one or more sleep-related QOL measures, 13,17,23,26,29,[33][34][35][36]42,44,47 with the most popular being the Pittsburgh Sleep Quality Index (PSQI; N = 8).…”
Section: Resultsmentioning
confidence: 99%
“…Search terms were developed with reference to Arber et al 11 by two authors, one a health economist (EW) and one an information specialist (NK). The search terms centred around the concepts of hospital patients, COVID-19 and health utility measures, including qualityadjusted life-years (QALYs), disability-adjusted life-years (DALYs) and survey measures such as EQ-5D, the Short Form (36) Health Survey (SF-36) and the Health Utilities Index (HUI). A full list of search strategies is included in the Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…These findings are consistent with a previous study which demonstrated a decrease in the symptoms of depression and anxiety whereas increased symptoms of insomnia among COVID-19 patients over time [ 64 ]. Additionally, another study indicated that there was no significant change in insomnia over time among COVID-19 patients [ 65 ]. Several factors may contribute to this pattern of insomnia exhibiting a different pattern than other symptoms of mental ill-health.…”
Section: Discussionmentioning
confidence: 99%